Big Data in the Modern Digital Economics and Statistics - O. V. STAVYTSKYI; R. L. PANTYEYEV (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article shows how the deployment of Big Data technologies is changing the logic of the formation and use of official statistics in the digital economy. It is substantiated that thanks to its efficiency, scale, diversity of sources and the ability to integrate heterogeneous information flows, Big Data enhances economic and statistical analysis. A range of challenges is outlined: fragmented infrastructure, shortage of qualified personnel, lack of established validation procedures, difficulties in ensuring confidentiality and data protection. A conceptual framework for assessing the quality of digital statistical information according to three criteria is proposed - stability, accessibility, structural completeness. The need for institutional strengthening of official statistics, harmonization with European standards and development of competencies in the field of data science to support evidence-based decision-making in the digital age is emphasized.